Measurement and control of magnetic thin films and devices using thermal gradients applied via suspended Si-N membranes - B. L. Zink (Science and Technology of Advanced Materials, 2025)
Magnetic thin films and nanostructures present a unique challenge for a range of thermal measurements, with important consequences for both fundamental physics and material science and applications. This paper reviews the unique capabilities for measurement and control of these systems using thermal gradients applied using micro- and nanofabricated silicon-nitride membrane platforms. Supporting a thin film or nanostructure removes bulk heat sinks from the tiny structure, enabling otherwise challenging or impossible measurements including thermal conductivity, Seebeck coefficient, Peltier coefficient, magnon drag, both the anomalous and planar Nernst effect, specific heat, and novel manifestations of thermally assisted spin transport. After providing some historical context and motivation and overviewing the design and fabrication of silicon-nitride membrane thermal platforms, example data for each of the measurements above is reviewed, and the paper concludes with a consideration of the outlook for measurements enabled by these techniques.